2019
DOI: 10.1007/s13300-018-0557-3
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Metformin and Sulfonylurea Monotherapies and Cancer Incidence: A Real-World Cohort Study in Shanghai, China

Abstract: IntroductionPrevious studies have shown that patients with type 2 diabetes mellitus have an increased risk of cancer. The use of antidiabetic medication (ADM) may play an important role in the cancer development. The relationship between oral ADM and cancer incidence has not been investigated in type 2 diabetes mellitus patients in mainland China yet.MethodsA community-based diabetes cohort was extracted from the Shanghai Community Diabetes Management System database, which is a patient registry from general p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…Although no direct tumorigenic properties have been described, two studies have pointed out high risk of cancer in individuals treated with sulfonylureas compared to those treated with glyburide [102] or insulin [103]. In contrast, other studies found no effect [104] or a protective effect [105]. This uncertainty highlights the search for appropriate comparison groups as the current challenge in evaluating the effectiveness of sulfonylureas.…”
Section: Sulfonylureasmentioning
confidence: 99%
“…Although no direct tumorigenic properties have been described, two studies have pointed out high risk of cancer in individuals treated with sulfonylureas compared to those treated with glyburide [102] or insulin [103]. In contrast, other studies found no effect [104] or a protective effect [105]. This uncertainty highlights the search for appropriate comparison groups as the current challenge in evaluating the effectiveness of sulfonylureas.…”
Section: Sulfonylureasmentioning
confidence: 99%
“…Ye et al in a population-based cohort study estimated the pancreatic cancer risk in 653 new-onset T2DM patients using Sus and revealed that sulphonylureas monotherapy was associated with significantly lower risk of pancreatic cancer [57].…”
Section: Sulphonylureasmentioning
confidence: 99%
“…Estudos sugerem que a metformina pode estar associada à redução no risco de câncer (DABROWSKI et al, 2017;KIM et al, 2018;KUO et al, 2019;WEN et al, 2019;YAO et al, 2019;YE et al, 2019) e a melhores prognósticos em pacientes com câncer (GUO et al, 2017;LI et al, 2017b;WAN et al, 2018;SHI et al, 2019).…”
Section: Diabetes Mellitusunclassified